Disinflationary Booms? - Merkl, Christian (Economics letters, 2013)
This paper shows that announced credible disinflations under inflation targeting lead to a boom in a standard New Keynesian model (i.e. a disinflationary boom). This finding is robust with respect to various parameterizations and disinflationary experiments. Thus, it differs from previous findings about disinflationary booms under monetary targeting.
WiSo-Import:2015-03-26:4818
Keywords: Inflation targeting; Disinflationary boom; disinflation